Kesesuaian Pengajuan Kasasi Atas Dasar Judex Facti Salah Menerapkan Hukum Dalam Perkara Narkotika Oleh Anggota Militer - Bhertty Chris Yudiasningrum (Sebelas Maret University, 2017)
This research aims to determine the suitability of the appeal on the basis misapplied the law in the case of narcotics by members of the military by Act No. 31 of 1997 on Military Justice. The method used is a normative legal research prescriptive and applied. The approach used is a case approach. Sources of legal materials used are primary and secondary legal materials, with materials analysis techniques that are legal syllogism deductive method. Cases of drug abuse conducted by Mustafa Kamal who is a member of the military has been in Decision Military Court I-03 Padang No. 124-K / PM-I-03 / AD / XII / 2013 sentenced pidan imprisonment of 1 (one) year and criminal additional fired from military duty. Appealed against the decision which is then severed by the High Military Court Decision I Field Number: 108-K / PMT-I / BDG / AD / X / 2014 that it upheld the verdict in advance. The defendant Mustafa Kamal then apply for an appeal against the decision on the grounds judex facti misapplied the law. The appeal by Defendant Mustafa Kamal was received by the Supreme Court and the Supreme Court Decision No. 88K / MIL / 2015 canceled the previous decision. Based on the study it can be concluded on the basis of appeals misapplied the law in accordance with the provisions of Article 239 of Law No. 31 of 1997. Thus, on the basis of appeals misapplied the law is acceptable. Keywords: Cassation, Narcotic, Military Members